Desain Kebaya Sunda Abad Ke-20 Studi Kasus di Bandung Tahun 1910-1980 - Irma Russanti (ITB Journal Publisher, LPPM ITB, 2007)
The female traditional outfits of Sunda are varied according to geography, history, social life, economy, and cultural transformations that have taken place for centuries. The similarity in both cultures and historical background had resulted in the similarity on structural design of the various female outfits in this area. This study focuses to identify various styles of kebaya Sunda that shared similarity of features. The word Sunda itself was used as a collective term, and apparently had a relation with the original place and culture of the kebaya wearers